Kinetics of Phosphate Adsorption by Alluvial Soils at Different Temperatures - Bala, Parveen; Bhardwaj, S.S.; Sidhu, P.S. (Asian Journal of Chemistry, 2010)
The kinetics of phosphate adsorption by alluvium derived soils was studied and data obtained were used to calculate various kinetic and thermodynamic parameters. The kinetics of phosphate adsorption could be described by second order reaction. For a particular time interval, the amount of phosphate adsorbed increased with increase in temperatue indicating endothermic nature of phosphate adsorption process.